ESG, Profitability and Leverage on Tax Aggressiveness: The Moderating Role of Firm Size in IDX-Listed Firms, 2020-2024 - Nabila Faiza Hakim; Kurnia (Ilomata International Journal of Tax and Accounting, 2026)
This research examines the effect of ESG, profitability, and leverage on tax aggressiveness, measured by the Cash Effective Tax Rate (CETR) with firm size as a moderating variable. The analysis focuses on firms listed on the Indonesia Stock Exchange from 2020-2024 period. Since the regression model uses CETR directly as a dependent variable, a lower CETR value indicates higher tax aggressiveness, while a higher CETR value indicates lower tax aggressiveness. Therefore, a negative regression coefficient is interpreted as an increase in tax aggressiveness, whereas a positive coefficient indicates a decrease in tax aggressiveness. A quantitative approach was employed using panel data regression and Moderated Regression Analysis (MRA). This study sample consisted of 41 companies selected via purposive sampling, resulting in 205 observations. The results show that ESG and profitability did not show a significant effect on tax aggressiveness. However, the study found that leverage has a statistically significant impact on tax aggressiveness. Furthermore, firm size weakness the effect of leverage on tax aggressiveness, thereby moderating the relationship between leverage and tax aggressiveness. In contrast, firm size does not exert a significant moderating effect on the relationships between ESG and tax aggressiveness, nor between profitability and tax aggressiveness. Although ESG performance and profitability do not significantly explain corporate tax aggressiveness during the study period, the findings indicate that debt policy remains the primary determinant of corporate tax aggressiveness.